A family case of a rare autoinflammatory disease associated with mutations in the NLRP3 and TNFRSF1A genes in the practice of a rheumatologist - Yu. D. Kurochkina; M. A. Korolev; E. A. Letyagina; V. S. Fishman; M. M. Gridina; E. S. Valeeva (Бюллетень сибирской медицины)
The article presents a clinical case of a rare autoinflammatory disease – a family case of Muckle – Wells syndrome. The diversity of clinical manifestations and the impossibility of confirming the diagnosis without a genetic study by DNA sequencing determine the complexity of and delay in the diagnosis. The development of severe complications and, as a consequence, a fatal outcome necessitates early diagnosis. The described clinical case demonstrates the importance of DNA sequencing for the timely diagnosis of the disease, the features of the disease course, and the familial nature of the disease. The diagnosis of Mackle – Wells syndrome in young family members before the development of severe complications will allow to start adequate and timely treatment and prevent the development of amyloidosis.